The Gendered Screen: Canadian Women Filmmakers - Austin-Smith, Brenda; Melnyk, George (Wilfrid Laurier University Press, 2010)
Discussions of established women filmmakers whose careers have produced major bodies of work, as well as newer filmmakers and new media artists.
OCLC: 729021166
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 5-Créatrice; _Nettoyé